2012
DOI: 10.1016/j.jbiomech.2011.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming cardiomyocyte mechanosensing by crosstalk between integrins and hyaluronic acid receptors

Abstract: The elastic modulus of bioengineered materials has a strong influence on the phenotype of many cells including cardiomyocytes. On polyacrylamide (PAA) gels that are laminated with ligands for integrins, cardiac myocytes develop well organized sarcomeres only when cultured on substrates with elastic moduli in the range of 10 kPa to 30 kPa, near those of the healthy tissue. On stiffer substrates (>60 kPa) approximating the damaged heart, myocytes form stress fiber-like filament bundles but lack organized sarcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 38 publications
3
61
0
Order By: Relevance
“…58 Endothelial cell alignment to shear stress was approximately 42% using similar measurements. 66 To further confirm the impact of the nanofibers on cell morphology, the aspect ratio of the nuclei of individual cells was determined (Figure 4E). Aligned scaffolds had a significantly increased aspect ratio over random scaffolds.…”
Section: Resultsmentioning
confidence: 99%
“…58 Endothelial cell alignment to shear stress was approximately 42% using similar measurements. 66 To further confirm the impact of the nanofibers on cell morphology, the aspect ratio of the nuclei of individual cells was determined (Figure 4E). Aligned scaffolds had a significantly increased aspect ratio over random scaffolds.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, engineered cells on 6-and 35-kPa substrates had defects in myofibril organization through overtension and myofibril rupture (35 kPa) or undertension and myofibril buckling (6 kPa) (48). Previous studies found that 10-kPa substrates yield useful cultures of immature primary neonatal murine CMs with physiological shape (21,23). Increasing substrate stiffness without controlling cell shape increases the force output of neonatal murine CMs (25) and unpatterned hPSC-CMs (24).…”
Section: Discussionmentioning
confidence: 99%
“…Neonatal ventricular rat cardiomyocytes were harvested from excised hearts of 1-to 3-day-old euthanized Sprague-Dawley rat pups using a cell isolation kit (Cellutron Life Technology, Baltimore, MD, cellutron.com) (7). Briefly, cells were isolated from the cardiac tissue of both ventricles.…”
Section: Methodsmentioning
confidence: 99%